INFLUENCE OF HISTORY AND CULTURE ON REGIONALISM: A CASE STUDY OF ASEAN - Sharma, Gourav; Kumar, Pardeep (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In the modern age, regionalism represents an important aspect of global politics, marked by the establishment and expansion of regional organizations that has reconstituted international relations. Regional cooperative frameworks have especially gained momentum in the post-Cold War era; that is a response to globalization, shift in the balance of power, and regional security concerns (Fawcett & Hurrell, 1995). These institutions-from the supranational to the local-became platforms of economic cooperation, political dialogue, and security collaboration-the building blocks of stability and development in the regions of the countries involved.